T-Follicular-Like CD8+ T Cell Responses in Chronic HIV Infection Are Associated With Virus Control and Antibody Isotype Switching to IgG - Romero-Martín, Luis; Tarrés-Freixas, Ferran; Pedreño-López, Núria; de la Concepción, Maria L. Rodríguez; Cunyat, Francesc; Hartigan-O'Connor, Dennis; Carrillo, Jorge; Mothe, Beatriz; Blanco, Julià; Ruiz-Riol, Marta; Brander, Christian; Olvera, Alex (Frontiers in Immunology, 2022)
T cell responses are considered critical for the in vivo control of HIV, but the contribution of different T cell subsets to this control remains unclear. Using a boosted flow cytometric approach that is able to differentiate CD4+ and CD8+ T cell Th1/Tc1, Th2/Tc2, Th17/Tc17, Treg and Tfh/Tfc-like HIV-specific T cell populations, we identified CD8+ Tfc responses that were related to HIV plasma viral loads and associated with rate of antibody isotype class switching to IgG. This favorable balance towards IgG responses positively correlated with increased virus neutralization, higher avidity of neutralizing antibodies and more potent antibody-dependent cell cytotoxicity (ADCC) in PBMCs from HIV controllers compared to non-controllers. Our results identified the CD8+ Tfc-like T-cell response as a component of effective virus control which could possibly be exploited therapeutically.